2009
DOI: 10.1143/jjap.48.052102
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of InP-Based Edge-Emitting Buried Heterostructure Laser Diodes Degraded by Forward-Biased Electrostatic Discharge Tests

Abstract: We investigated the forward-biased electrostatic discharge (ESD)-induced degradation that is one of the important reliability issues for InPbased edge-emitting buried heterostructure laser diodes. Although it has been suggested that the degradation mechanism is related to optical damage, the detailed mechanism has not been established. Thus, we carried out failure analysis. Two elliptically shaped degraded regions, which were introduced by the first and second ESD pulses, were observed in an active layer. A pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Although the ESD tolerance of facet-uncoated FP LDs was 1.2 kV, that of facet-coated FP LDs was higher than 3 kV. 8 This difference was mainly caused by suppression of facet oxidation. We also found that ion cleaning of the facet just prior to coating influences the ESD tolerance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the ESD tolerance of facet-uncoated FP LDs was 1.2 kV, that of facet-coated FP LDs was higher than 3 kV. 8 This difference was mainly caused by suppression of facet oxidation. We also found that ion cleaning of the facet just prior to coating influences the ESD tolerance.…”
mentioning
confidence: 99%
“…[5][6][7] Forward-biased ESD-induced degradation is caused by melting of the active layer at the facet following optical absorption. 6,8 In contrast, reverse-biased ESD-induced degradation is caused by destruction of the p-n junction by the electric field. 7 Although these ESD-induced degradation mechanisms of GaInAsP / InP LDs have been clarified, those of AlGaInAs/ InP LDs remain uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation